1976
DOI: 10.1002/eji.1830061212
|View full text |Cite
|
Sign up to set email alerts
|

Diseases caused by reactions of T lymphocytes to in compatible structures of the major histocompatibility complex. I. Autoimmune hemolytic anemia

Abstract: Diseases caused by reactions of T lymphocytes to in com pat i ble structures of the major h istocom pa t i b i I i t y complex 1. Autoimmune hemolytic anemia"The capacities of various lymphoid cells from C57BL/10 donors t o induce antibodies against red blood cells (RBC) in (C57BL/10 x DBA/2)Fl recipients were compared: cortisone-resistant thymocytes were more potent inducers than spleen cells, and bone marrow cells were ineffective. This established a need for parental T lymphocytes in the induction of Coombs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Another possible outcome of the GVHR is a chronic GVHD which can lead to different conditions, such as lymphadenopathy (5,6), immune complex glomerulonephritis (6,7), and formation of multiple autoantibodies (8)(9)(10)(11). Previous analyses performed in nonirradiated Fa mice have shown that there are two minimal, essential requirements for the induction of the symptoms of chronic GVttD: immunocompetent T lymphocytes must be present in the donor cell inoculum and they must be able to react to incompatible H-2 structures of the recipient (5-7, 9, 11).…”
mentioning
confidence: 99%
“…Another possible outcome of the GVHR is a chronic GVHD which can lead to different conditions, such as lymphadenopathy (5,6), immune complex glomerulonephritis (6,7), and formation of multiple autoantibodies (8)(9)(10)(11). Previous analyses performed in nonirradiated Fa mice have shown that there are two minimal, essential requirements for the induction of the symptoms of chronic GVttD: immunocompetent T lymphocytes must be present in the donor cell inoculum and they must be able to react to incompatible H-2 structures of the recipient (5-7, 9, 11).…”
mentioning
confidence: 99%
“…Ig Allotype. Antisera specific for the Ig-I b allotype of B10 and the Ig-1 c allotype of DBA/2, respectively, were prepared as described (23). The anti-Ig-1 c serum was used at a constant dilution of 1 in 3 and the anti-Ig-1 h serum at a constant dilution of 1 in 9.…”
Section: Determination Of Hemopoiesis By Incorporation Of 5efementioning
confidence: 99%
“…These examples illustrate the general principle that a wide range of transient viral infections could initiate immune reactions that might interact with structural components of host cells such as histocompatibility antigens or viral proteins incorporated in cell membranes. Moreover, T lymphocyte reactions against histocompatibility antigens altered by virus infection could lead to true autoimmune reactions (Gleichmann and Gleichmann, 1976). Viral persistence in lymphoreticular cells (Fig.…”
Section: Rheumatoid Arthritis a Virus Disease?mentioning
confidence: 99%